2020
DOI: 10.1098/rsos.191858
|View full text |Cite
|
Sign up to set email alerts
|

A hybrid gravity and route choice model to assess vector traffic in large-scale road networks

Abstract: Human traffic along roads can be a major vector for infectious diseases and invasive species. Though most road traffic is local, a small number of long-distance trips can suffice to move an invasion or disease front forward. Therefore, understanding how many agents travel over long distances and which routes they choose is key to successful management of diseases and invasions. Stochastic gravity models have been used to estimate the distribution of trips between origins and destinations of agents. However, in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 37 publications
2
8
0
Order By: Relevance
“…The trip counts were highest between subbasins close to major cities, as anglers show a strong preference for fishing destinations near their homes. This agrees well with earlier studies (Drake & Mandrak, 2010;Papenfuss et al, 2015;Fischer et al, 2020). At the same time, we found that the subbasins' attractiveness to anglers varied strongly, emphasizing the need for considering covariates capturing this heterogeneity when estimating angler traffic.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The trip counts were highest between subbasins close to major cities, as anglers show a strong preference for fishing destinations near their homes. This agrees well with earlier studies (Drake & Mandrak, 2010;Papenfuss et al, 2015;Fischer et al, 2020). At the same time, we found that the subbasins' attractiveness to anglers varied strongly, emphasizing the need for considering covariates capturing this heterogeneity when estimating angler traffic.…”
Section: Discussionsupporting
confidence: 92%
“…Without this distinction (e.g. Drake & Mandrak, 2010;, residuals would be solely attributed to the stochasticity in the individuals' decisions, and the dispersion parameter would be overestimated (Fischer et al, 2020). Then, low-traffic angler flows gain an inordinate weight when the model is fitted to observations, resulting in decreased model accuracy (see SI F).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, libraries for automatic differentiation are widely available and easy to use (e.g. Albertsen et al 2015), making RVM applicable to complex models (see Fischer et al 2020, for such an application of RVM). 3.…”
Section: Discussionmentioning
confidence: 99%
“…To define an appropriate function to compute i and a j based on the covariates, we categorized the covariates into groups  (Table 1), each accounting for a different component that is necessary for high angler traffic between an origin and a destination (cf. Fischer et al, 2020). For each origin or destination k, we assigned the score…”
Section: Submodels For Day Suitability Angler Activeness and Destinat...mentioning
confidence: 99%